Mechanical Circulatory Support for Advanced Heart Failure A Texas Heart Institute/Baylor College of Medicine Approach (Springer International Publishing, 2018)
This book provides the most up to date information on every aspect of clinical care relating to patients with advanced heart failure who require mechanical circulatory support as a treatment strategy. The book begins with an extensive description of the preoperative patient selection process as well as preoperative medical optimization, including bridge to bridge strategies with short-term devices. The book then transitions into a description of a variety of surgical implantation techniques with special considerations for reoperative surgery. A chapter on intraoperative anesthesia management is specifically focused on intraoperative issues relating to MCS patients. Subsequent chapters focus on perioperative management as well as long-term management of patients on MCS, including optimization of a patient's LVAD speed. A dedicated chapter on the diagnosis of device thrombosis as well as surgical techniques and outcomes associated with device exchanges is also included. The book also summarizes the national and international outcomes data for using MCS as a bridge to transplant and destination therapy. There is also a chapter on the utility of stem cells as an adjunct technique for inducing myocardial recovery. Finally, the book has chapters on complications of MCS, management of right ventricular failure, and the future of MCS.